Incidental positive lymph nodes in patients with papillary thyroid cancer is independently associated with recurrent disease. Issue 3 (1st June 2017) - Kluijfhout, Wouter P.; Drake, Frederick T.; Pasternak, Jesse D.; Beninato, Toni; Vriens, Menno R.; Shen, Wen T.; Gosnell, Jessica E.; Liu, Chienying; Suh, Insoo; Duh, Quan‐Yang
Abstract : Background and Objectives: Pathological examination occasionally reveals incidental central lymph nodes metastasis (iLNM) after thyroidectomy for patients with papillary thyroid cancer (PTC) who did not undergo compartment‐orientated lymphadenectomy. We aimed to investigate the risk of recurrence for patients with iLNM. Methods: We conducted a retrospective review of all patients undergoing total thyroidectomy for PTC (January 2000 to January 2010). Patients with distant metastases, central‐ or lateral neck dissection and pre‐operative suspicious lymph nodes (by ultrasound or clinical examination) were excluded. The association between iLNM and recurrent disease was investigated using Kaplan‐Meier survival estimates and Cox proportional hazards analysis. Results: 225/1000 patients had incidental nodes after total thyroidectomy for PTC. 183 were node‐negative and 42 had iLNM. Mean age was 46 years and 201 (89%) were women. Mean number of resected nodes was 2.3. Disease recurred in 8/183 (4.4%) of patients with N0 versus 7/42 (17%) with iLNM. After adjusting for other factors, iLNM was independently associated with recurrent disease (hazard ratio = 4.01 [95% CI 1.21–13.3]). Conclusions: Positive incidental lymph nodes are independently associated with recurrent disease in patients with PTC. These patients should therefore be monitored more carefully.